Sexual Health Education Among Autism Adolescents in Special Schools - Luluk Fauziyah; Munawir Yusuf; Joko Yuwono (Research Synergy Foundation, 2023)
Every learner, including those with autism, must be taught about sexual health education. Teachers have a crucial role to play in educating autistic adolescents about sexual health while they are in school. However, many teachers face confusion while teaching sexual education to autistic adolescent students. This research aims to describe the problem of sexual health education in autistic adolescents and the need for learning media to teach sexual health education to autistic adolescents in Special Schools. This study used a qualitative approach. Data was collected through interviews with teachers of autistic students in Special Schools. This research was conducted in 3 (three) special schools in Solo Raya, Indonesia: SLB A, SLB B, and SLB C. The subjects in this study were three teachers of autistic students. The research instrument used interviews with teachers regarding sexual health education issues and the need for instructional media to teach sexual education. The results of the study show that there was a main problem regarding teaching sexual education for autistic students; teachers with autistic adolescents experience confusion in teaching sexual education for autistic adolescents because there are no props or media that are suitable for autistic characteristics. Autism students more easily accept learning using visual-based media. This research's limitation is the sample, which only uses a small sample. This research was only conducted on teachers of autistic students in the Special Schools setting. Based on previous research on sexual education aimed at students with disabilities in general, the novelty of this study is to describe the problems of sexual education in autism students in the adolescent age category.